The Hollywood romantic comedy : conventions, history, controversies - Grindon, Leger, 1949- (Malden, MA : Wiley-Blackwell, 2011)
The most up-to-date study of the Hollywood romantic comedy film, from the development of sound to the twenty-first century, this book examines the history and conventions of the genre and surveys the controversies arising from the critical responses to these films.
Introduction -- History, cycles and society -- Thinking seriously about laughter and romance -- What is the trouble in paradise? : Trouble in paradise (1932) -- Jailbreak : His girl friday (1940) -- The home front romantic comedy and The miracle of Morgan's Creek (1944) -- Anatomy lesson : Adam's rib (1949) -- Riding sidesaddle in Some like it hot (1959) -- Counter conventions and cultural change in The graduate (1967) -- The trials of partnership in Annie Hall (1977) -- Friendship, sex and courtship in When Harry met Sally (1989) -- Parody and the grotesque in There's something about Mary (1998) -- Women's ambivalence in Waitress.
Includes bibliographical references and index.
Print version record.
Keywords: Romantic comedy films -- United States -- History and criticism; Love in motion pictures; Fine Arts; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Love in motion pictures; Romantic comedy films; United States; Electronic books; Criticism, interpretation, etc